1992
DOI: 10.2140/pjm.1992.155.295
|View full text |Cite
|
Sign up to set email alerts
|

Lp-Fourier transforms on nilpotent Lie groups and solvable Lie groups acting on Siegel domains

Abstract: JUNKOINOUEWe study Fourier transforms of Z/-functions (1 < p < 2) on nilpotent Lie groups and affine automorphism groups of Siegel domains. We get an estimate for the norm of the LP -Fourier transform for certain classes of nilpotent Lie groups. For affine automorphism groups, which are nonunimodular, we give an explicit definition of LP -Fourier transform, and obtain an estimate for the norm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…1. It is important to note that since the best constant for Young's inequality on locally compact topological groups is always less than 1 [41], Corollary 2 does not offer any improvement to the theory, however it is nonetheless included in this paper for the sake of context; we refer the reader to [23,35,39,41] for further details on Young's inequality in abstract settings. We remarked earlier on that Theorem 2 is an example of an affine-invariant inequality, in the sense that the left-hand side is invariant under the natural action A :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. It is important to note that since the best constant for Young's inequality on locally compact topological groups is always less than 1 [41], Corollary 2 does not offer any improvement to the theory, however it is nonetheless included in this paper for the sake of context; we refer the reader to [23,35,39,41] for further details on Young's inequality in abstract settings. We remarked earlier on that Theorem 2 is an example of an affine-invariant inequality, in the sense that the left-hand side is invariant under the natural action A :…”
Section: Resultsmentioning
confidence: 99%
“…BL(L, p) det(L m+1 L * m+1 ) − 1Proof By duality, (6) is equivalent to the boundG φ(x) ˚m j=1 f j j−1 l=1 1 p l (x)dμ(x) deg(G) φ L r (G) m j=1 f j L p j(G) (35). For 1 ≤ j ≤ m, define the nonlinear maps B j : G m → G, B j (x 1 , .…”
mentioning
confidence: 99%
“…We give a proof of this corollary in section 5. It is important to note that since the best constant for Young's inequality on locally compact topological groups is always less than one [40], Corollary 1.7 does not offer any improvement to the theory, however it is nonetheless included in this paper for the sake of context; we refer the reader to [23,34,38,40] for further details on Young's inequality in abstract settings. We remarked earlier on that Theorem 1.5 is an example of an affine-invariant inequality, in the sense that the left-hand side is invariant under the natural action A : B j Þ Ñ B j ˝A of GL n pRq on the class of quasialgebraic data, however this inequality in fact exhibits a more general diffeomorphism-invariance property, as described by the following proposition.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Fournier [4] showed that the norm kF p .G/k D 1 if and only if G has a compact open subgroup. Now, suppose G D exp g is a connected and simply connected nilpotent Lie group with Lie algebra g. Some estimates have been achieved for various examples and cases in this class by earlier works of Russo [9], [10], and [11], Klein and Russo [8], Inoue [6], Baklouti, Smaoui and Ludwig [1]. Let us recall that the unitary dual b G of a connected and simply connected nilpotent Lie group G is parameterized by the coadjoint orbits of G on the dual space g of g by the orbit method.…”
Section: Introductionmentioning
confidence: 99%